Structure and functional studies of N-terminal Cx43 mutants linked to oculodentodigital dysplasia - Shao, Qing (The American Society for Cell Biology, 2012)
Mutations in the gene encoding connexin-43 (Cx43) cause the human development disorder known as oculodentodigital dysplasia (ODDD). In this study, ODDD-linked Cx43 N-terminal mutants formed nonfunctional gap junction–like plaques and exhibited dominant-negative effects on the coupling conductance of coexpressed endogenous Cx43 in reference cell models. Nuclear magnetic resonance (NMR) protein structure determination of an N-terminal 23–amino acid polypeptide of wild-type Cx43 revealed that it folded in to a kinked α-helical structure. This finding predicted that W4 might be critically important in intramolecular and intermolecular interactions. Thus we engineered and characterized a W4A mutant and found that this mutant formed a regular, nonkinked α-helix but did not form functional gap junctions. Furthermore, a G2V variant peptide of Cx43 showed a kinked helix that now included V2 interactions with W4, resulting in the G2V mutant forming nonfunctional gap junctions. Also predicted from the NMR structures, a G2S mutant was found to relieve these interactions and allowed the protein to form functional gap junctions. Collectively, these studies suggest that the nature of the mutation conveys loss of Cx43 function by distinctly different mechanisms that are rooted in the structure of the N-terminal region.